2022
DOI: 10.1136/bmjgh-2022-010020
|View full text |Cite
|
Sign up to set email alerts
|

Turning the tide on female genital mutilation in a high prevalence country: a programmatic data analysis for Sudan’s comprehensive health sector response, 2016–2018

Abstract: Sudan has about 87% of females aged 15–49 years living with female genital mutilation (FGM), mostly performed by midwives (64%). In 2016, the Federal Ministry of Health (FMoH) adopted the WHO’s global strategy to stop healthcare providers from performing FGM. Our review of activity reports from 2016 to 2018 found the format of activities (N=95) was mainly meetings (58%) and trainings (31%) with median costs of US$10 645 and US$14 964, respectively. The FMoH (57%) and student/professional associations (25%) imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Studies have shown that monitoring and evaluation (M&E) is an effective strategy in improving health workers’ practice in low-income settings 15 16. A study which assessed Sudan’s health programmatic interventions found no FGM-related data at facility level,6 suggesting limited tracking for M&E and low accountability for health workers on the quality of care and FGM medicalisation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that monitoring and evaluation (M&E) is an effective strategy in improving health workers’ practice in low-income settings 15 16. A study which assessed Sudan’s health programmatic interventions found no FGM-related data at facility level,6 suggesting limited tracking for M&E and low accountability for health workers on the quality of care and FGM medicalisation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, because the events occurred 3–5 years prior to the study, there may have been recall bias. Our strategy to mitigate this through sharing questions in advance and recommending review of their programme reports seemed to reduce this as the activities discussed by respondents matched the activities we found in previous programmatic data review 15…”
Section: Discussionmentioning
confidence: 99%
“…The health interventions funded by the SFFGC programme were guided by WHO’s four pillars of action: strengthen governance and funding (pillar 1); increase health workers’ knowledge and skills (pillar 2); improve monitoring and evaluation (M&E) and accountability (pillar 3); and create a supportive environment (pillar 4) 6. Between 2016 and 2018, Sudan had significant achievements in the health component of SFFGC programme,5 prompting further in-depth study to understand how and why this occurred. The present study contributes to a much-needed programmatic evidence base on complex health interventions in low-income FGM prevalent settings, in contrast to the current body of evidence, which has addressed singular health interventions or factors affecting FGM-related health interventions in high-income settings 7–15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could explained partly because the foundational activities were not rolled out to scale together with the absence of FGM related monitoring and evaluation systems. 16 Strengthening monitoring and evaluation of foundational activity processes would need to go hand in hand during implementation and continued thereafter.…”
Section: Reflections On the Scale Up Approachmentioning
confidence: 99%